Iron Deficiency and Cognitive Underachievement - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The relationship between iron deficiency and cognitive test scores among 5398 children, 6 to 16 years old, was studied at the University of Rochester School of Medicine, NY, by analysis of data obtained from the National Health and Nutrition Examination Survey III 1988-1994.